Characteristics of patients with shingles admitted to a district general hospital. Issue 868 (February 1998) - Morgan, R.; King, D.
Abstract : Little is known about why some patients with shingles are admitted to hospital. We reviewed 72 case notes from a list of 80 patients admitted to hospital with shingles over a six-year period. Pain was the main complaint of the patients admitted, most of whom were elderly and lived alone. The commonest site of involvement in hospital admissions was the eye (herpes zoster ophthalmicus). Diagnosis of shingles was made after admission in 12 patients, eight of whom had originally been diagnosed as having an acute medical or surgical condition. We conclude that the prodromal phase of shingles may lead to misdiagnosis.